2005
DOI: 10.1073/pnas.0508945102
|View full text |Cite|
|
Sign up to set email alerts
|

Human stem/progenitor cells from bone marrow promote neurogenesis of endogenous neural stem cells in the hippocampus of mice

Abstract: Stem/progenitor cells from bone marrow and other sources have been shown to repair injured tissues by differentiating into tissue-specific phenotypes, by secreting chemokines, and, in part, by cell fusion. Here we prepared the stem/progenitor cells from human bone marrow (MSCs) and implanted athem into the dentate gyrus of the hippocampus of immunodeficient mice. The implanted human MSCs markedly increased the proliferation of endogenous neural stem cells that expressed the stem cell marker Sox2. Labeling of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
273
0
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 383 publications
(300 citation statements)
references
References 45 publications
(27 reference statements)
16
273
0
6
Order By: Relevance
“…51 To further substantiate this hypothesis, it should be noted that studies have shown that inflammatory processes have a negative effect on cell proliferation. 52,53 As such, molecular and behavioral recovery can be stimulated despite the fact that, as a result of the inflammatory and rejection processes, many of the transplanted cells are eventually absorbed by the host immune system.…”
Section: Discussionmentioning
confidence: 98%
“…51 To further substantiate this hypothesis, it should be noted that studies have shown that inflammatory processes have a negative effect on cell proliferation. 52,53 As such, molecular and behavioral recovery can be stimulated despite the fact that, as a result of the inflammatory and rejection processes, many of the transplanted cells are eventually absorbed by the host immune system.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, MSC can protect axons and improve neuronal survival [4,9,10] releasing antiapoptotic [11] or antioxidant molecules [12]. It has been also reported that MSC may foster endogenous neurogenesis [13] and oligodendrogenesis [14][15][16] not only by direct release of trophic factors but also by stimulating glial cells to secrete molecules leading to neuron survival and proliferation of the endogenous neural precursor cells [17].…”
Section: Introductionmentioning
confidence: 99%
“…14,21 Similarly, injection of human MSCs into the hippocampus of normal mice resulted in a significant increase in neurogenesis, originating primarily from host neural stem cells. 8 Moreover, the engraftment of neural stem cells or MSCs in the hippocampus and dentate gyrus resulted in increased neurogenesis and induced an improved behavioral phenotype in prenatal heroin exposure and in apolipoprotein E knockout mice, respectively. 22,23 In this study, we therefore analyzed the possible therapeutic potential of MSCs in depression.…”
Section: Introductionmentioning
confidence: 99%
“…7 Moreover, transplantation of MSCs in the central nervous systems prevents apoptosis and promotes neurogenesis (proliferation and differentiation) of 'host' neural cells and stem cells in the engrafted site. [7][8][9] MSCs were therefore suggested as candidates for treating a variety of neurodegenerative diseases, in particular Parkinson's disease, multiple sclerosis, cerebral hemorrhage and brain cancer. [10][11][12][13] Neurogenesis is a continuous process of the formation of new neurons, which occurs in the dentate gyrus in the hippocampus throughout life.…”
Section: Introductionmentioning
confidence: 99%